IOS Cloud Development For Dummies. - Goldstein, Neal (--For dummies., 2012)
Want to create robust, data-driven, iOS cloud apps? This book makes it easier! Apple's mobile operating system (iOS) supports iPhones, iPads, iPods and other Apple devices, and while even beginners can now develop apps to run just on these devices themselves, sometimes you want to create an app with more heft. Applications such as live weather reports or multi-player games require a lot of data to be pulled from outside & mdash;often from cloud-based Web Services, such as Google or Amazon. This book, written by application development experts Sujee Maniyam and Neal Goldstein, shows you how to we.